Managing Successful Conclusion of the Third Biennial Review (March 2020), with the EU, Leading to Retention of Pakistan’s GSP+ Status - Shouket, Aamir (Journal of Pakistan Administration, 2022)
European Union (EU) is a unique integration of economic and political cooperation between 27 member states. The EU is a supranational mechanism in which member states have given up some of their sovereign rights to strengthen the Union’s structure.  Acting as a group, EU has broadened its relations with non-European countries over the years. Pakistan has always enjoyed reasonably good relations with individual EU member countries at the bilateral level, as well as, with the collective EU mechanismsbased in Brussels. This relationship has been moving on in an upward trajectory and encompasses leadership level interactions, high-level military contacts, parliamentary exchanges, agreements and dialogue frameworks. Trade, however, remains the central feature of Pakistan’s relations with the EU; the latter serves as the top market for Pakistani exports, with almost one third of Pakistan’s total exports going to EU member states.
Keywords: EU; Pakistan; GSP+ Status; cooperation